Biotropic parameters of electromagnetic radiation for regeneration of animal damaged bone tissue - Orel, Oleksandr; Орел, Олександр Миколайович; Орел, Александр Николаевич; Vlasov, Illia; Orel, M. (My University, 2017)
The development of effective medication-free treatment and means of animal injuries treatment is urgent task. The optimal parameters of electromagnetic field of ultra-high frequency range interacting with the bone tissues of animals have been determined. The aim of the work is to identify the high-frequency range of the electromagnetic field parameters in interaction with animal tissues using the developed mathematical model. The dependence of electric component amplitude of magnetic frequency field was investigated. It has been proved that the dimensions of the limbs and internal tissues significantly affect the internal distribution of the electromagnetic fields. The results of experimental studies have made it possible to determine the optimal frequency, power and radiation source arrangement for the injury treatment of different animal species. The application of electromagnetic radiation with optimal parameters intensifies metabolism on the diseased cells membrane level and assists more rapid recovery of the injured bone tissue.
Keywords: injuries; ultra-high frequency; parameters; mathematical model; metabolism; cells membrane